Evaluating performance of international closed-end funds in US - SUN, MEI (2007)
The closed-end funds are the growing field for the investors and researchers. Especially in US, the international closed-end funds develop rapidly, which have influenced the global investment strategy. This dissertation chooses 20 US based international closed-end funds through the time period 2004 to 2007. The quantified method is used in the part of Methodology, the CAPM model is employed as the basic model to measure the performance. The MSCI AC World ex U.S. Index is employed to compare the international closed-end funds performance with the world market. There are three measurements index applied in evaluating the performance-Jensen's alph, Treynor index and Sharpe ratio. However, there are some limits for the study, since the limits of CAPM and the measurement benchmark. Besides, the technique drawbacks also result in the research limits.